Uma proposta do uso de building information modeling associado à engenharia simultânea para desenvolvimento de projetos em AEC - Azevedo, Diogo Martins (2022)
With the growing di usion of the use of BIM (Building Information Modeling) technologies, within the elds of Architecture and Civil Engineering, it shows that the results arising from collaborative work have brought great bene ts to these areas, since the designation of project project until its execution and operation. Furthermore, the use of this methodology facilitates the compatibility of di erent project disciplines, since it is possible to use the IFC (Industry Foundation Class) communication protocol for the project incorporated as disciplines in a single model, which is named federated model . However, creating separate models and then unifying them in a single point generates a large number of incompatibilities between the developed disciplines. Thus, this work o ers the use of a server system for the development of electrical and hydraulic disciplines with measurement of incompatibilities between these disciplines and those that were imported. In general, the results obtained in this report communicate satisfactory results, since the disciplines developed in a collaborative work system had 137 incompatibilities, while the others had an overall average of 1968 incompatibilities.